Evaluating herbicide-resistant Lolium perenne ssp. multiflorum germination and their response to safflower’s allelopathic effects - Longas, María de las Mercedes (2025)
Lolium perenne ssp. multiflorum (Lam) Husnot, commonly known as ryegrass, is a globally important weed with documented resistance to multiple herbicide modes of action. The germination and emergence responses of both susceptible and herbicide-resistant ryegrass phenotypes to environmental conditions may differ between them. To develop sustainable management strategies that reduce herbicide use, the inclusion of allelopathic crops such as Carthamus tinctorius (safflower) is promising. In the semi-arid temperate region of Argentina, specifically in the southwest of Buenos Aires Province, safflower is regarded as an alternative winter crop that is being cultivated for edible oil production. Therefore, understanding the effect of different safflower varieties on the morphophysiological seed traits of herbicide-resistant ryegrass phenotypes is crucial for optimizing management strategies. In this context, this study aims to: 1) evaluate the germination capacity of three ryegrass populations (Lp)—a susceptible population (1LOLG1), a population resistant to both ALS and ACCase inhibitors (1LOLG2), and a population resistant to EPSPS, ALS, and ACCase inhibitors (1LOLG3)— under alternate temperature and water potential regimes in the laboratory, and 2) to assess the effect of allelopathic substances, remaining in the soil or in residual leaves, from five safflower genotypes (CW99 OL, RCJ3, WSRC01, Montola 2000, and RM NAPOSTÁ) on the germination and initial growth (coleoptile and radicle length) of Lp. Seed weight differed among Lp (1LOLG1<1LOLG2<1LOLG3; p<0.01), while cumulative germination followed the opposite pattern (1LOLG1>1LOLG2>1LOLG3; p<0.05). 1LOLG3 exhibited the highest hydrotime constant and the lowest minimum water potential for germination values (p<0.05). The safflower genotypes differed in their allelopathic potential; CW99 OL leaves reduced germination by 20% in all Lp. Conversely, Montola 2000 soil stimulated germination. Coleoptile length was mostly affected in the Lolium resistant populations, indicating significant allelopathic effects of Montola 2000, WSRC01, and RM NAPOSTÁ. These results suggest that safflower can negatively impact the establishment of herbicide-resistant ryegrass seedlings, that could be useful information to integrated management strategies.